Integrating RNA-Seq With GWAS Reveals a Novel SNP in Immune-Related HLA-DQB1 Gene Associated With Occupational Pulmonary Fibrosis Risk: A Multi-Stage Study - Zhou, Yan; Zhang, Yingyi; Zhao, Rui; Cheng, Zhounan; Tang, Minzhu; Qiu, Anni; Dong, Yang; Lu, Yihua; Lian, Yulong; Zhuang, Xun; Tian, Tian; Wang, Wei; et al. (Frontiers in Immunology, 2022)
Objective: To evaluate the association between single-nucleotide polymorphisms (SNPs) in RNA-seq identified mRNAs and silicosis susceptibility. Methods: A comprehensive RNA-seq was performed to screen for differently expressed mRNAs in the peripheral blood lymphocytes of eight subjects exposed to silica dust (four silicosis cases and four healthy controls). Following this, the SNPs located on the shortlisted mRNAs, which may affect silicosis susceptibility, were screened through silicosis-related genome-wide association studies (GWAS) (155 silicosis cases and 141 healthy controls), whereas functional expression quantitative trait locus (eQTL)-SNPs were identified using the GTEx database. Finally, the association between functional eQTL-SNPs and silicosis susceptibility (194 silicosis cases and 235 healthy controls) was validated. Results: A total of 70 differentially expressed mRNAs (fold change > 2 or fold change < 0.5, P < 0.05) was obtained using RNA-seq. Furthermore, 476 SNPs located on the shortlisted mRNAs, which may affect silicosis susceptibility (P < 0.05) were obtained using GWAS, whereas subsequent six functional eQTL-SNPs were identified. The mutant A allele of rs9273410 in HLA-DQB1 indicated an increase in silicosis susceptibility in the validation stage (additive model: odds ratio (OR)= 1.31, 95% confidence interval (CI) = 0.99–1.74, P = 0.061), whereas the combination of GWAS and the validation results indicated that the mutant A allele of rs9273410 was significantly associated with increased silicosis susceptibility (additive model: OR = 1.35, 95% CI =1.09–1.68, P = 0.006). Conclusion: The mutant A allele of rs9273410 was associated with increased silicosis susceptibility by modulating the expression of HLA-DQB1.